PROGRAM OF RECREATIONAL AND HEALTH ACTIVITIES FOR ADOLESCENTS WITH CHARACTER'S ACCENTUATIONS - Vorobiova A.V (Kharkov National Pedagogical University, 2012)
The problem of using psychosomatic approach for correction the behavior of adolescents with character's accentuations was considered. The author's program of recreational and health activities for adolescents was grounded and offered, taking into account the level of social adaptation and psychological features of character. The researches were conducted on the basis of secondary schools № 5, 7, 11 of the Romny town, Sumy region with 12-16 years old teens (n=412), including 218 girls and 194 boys. It is determined that psychosomatic approach in health and recreation program provides for the development and planning means and methods that influence not only on the level of somatic and physical health, but also on the structure of adolescents' personality. It is recommended the author's program, that consists of three stages and solved the three groups of problems: health, training and educational, was developed and inculcated in an educational process.